Cover Feature: Structure‐ and Interaction‐Based Design of Anti‐SARS‐CoV‐2 Aptamers (Chem. Eur. J. 12/2022). Issue 12 (19th February 2022) - Mironov, Vladimir; Shchugoreva, Irina A.; Artyushenko, Polina V.; Morozov, Dmitry; Borbone, Nicola; Oliviero, Giorgia; Zamay, Tatiana N.; Moryachkov, Roman V.; Kolovskaya, Olga S.; Lukyanenko, Kirill A.; Song, Yanling; Merkuleva, Iuliia A.; et al.
Abstract : Digital drug design reveals DNA aptamers binding SARS‐CoV‐2 : A hybrid in silico et vitro approach, structure and interaction‐based drug design, has been developed to create highly specific DNA aptamers for the receptor‐binding domain of the SARS‐CoV‐2 spike protein. The structure and binding affinity of the aptamers were validated by small‐angle X‐ray scattering, flow cytometry, and fluorescence polarization. This approach offers a blueprint for the straightforward design of targeting molecules for new pathogens and emerging variants. More information can be found in the Research Article by Y. Alexeev, M. V. Berezovski, A. S. Kichkailo, et al. (DOI: 10.1002/chem.202104481 ).